2023
DOI: 10.1021/acsanm.3c02079
|View full text |Cite
|
Sign up to set email alerts
|

Nanolaponite/Comb Polymer Composite as a Rheological Modifier for Water-Based Drilling Fluids

Abstract: During the drilling of deep/ultradeep wells, water-based drilling fluids (WBDFs) often experience harsh conditions of ultrahigh temperature and high salt. Ultrahigh temperatures and high salts cause rheological instability in drilling fluid, reducing its suspension and cutting-carrying capacity. In this study, a comb polymer, P-TPEG with isopentenol polyoxyethylene ether (TPEG) as the side chain, was prepared via free radical polymerization in an aqueous solution and then compounded with nanolaponite (LAP) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(93 reference statements)
0
0
0
Order By: Relevance
“…The new LAP/isopentenol polyoxyethylene ether composite enhances the rheological properties of water-based drilling fluids under various conditions, including before and after aging at 240 °C, and it demonstrates resistance to 15% NaCl [ 173 ]. In water-based drilling fluids, the combination of LAP, isopentenol polyoxyethylene ether, and bentonite creates a flexible and robust network, allowing for better suspension and efficient transport of debris.…”
Section: Laponite ® Applicationsmentioning
confidence: 99%
“…The new LAP/isopentenol polyoxyethylene ether composite enhances the rheological properties of water-based drilling fluids under various conditions, including before and after aging at 240 °C, and it demonstrates resistance to 15% NaCl [ 173 ]. In water-based drilling fluids, the combination of LAP, isopentenol polyoxyethylene ether, and bentonite creates a flexible and robust network, allowing for better suspension and efficient transport of debris.…”
Section: Laponite ® Applicationsmentioning
confidence: 99%
“…This stabilizes the spatial network structure among drilling fluid constituents, 48 resulting in improved filtration and rheological performance of drilling fluids under high-temperature, high-salt conditions. 45,49 In our previous studies, we have demonstrated that polymers undergo thermal degradation in high-temperature environments. 50 Utilizing the destruction of the polymer network structure at high temperatures releases polymer nanoparticles to plug the pores of the filter cake, thereby maintaining the filtration performance of drilling fluids under high-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…LAP serves as a dispersant, suspending agent, and viscosifier, demonstrating excellent high-temperature performance when combined with bentonite-based slurries. Furthermore, LAP can adsorb onto polymer chains via electrostatic interactions and hydrogen bonding , or be incorporated into the spatial network structure of polymers through graft copolymerization, , enhancing polymer thermal stability. This stabilizes the spatial network structure among drilling fluid constituents, resulting in improved filtration and rheological performance of drilling fluids under high-temperature, high-salt conditions. , …”
Section: Introductionmentioning
confidence: 99%